The jurassic-cretaceous boundary controversy: its determination in the neuquen basin, argentina using magnetostratigraphy and cyclostratigraphy - Iglesia Llanos, Maria Paula (2017)
The J-K boundary is controversial at a global scale. Recently, it has been proposed that the J-K could be defined through microfossils (i.e. calpionellids) and/or magnetostratigraphy. The J-K boundary is comprised within the Vaca Muerta Formation that crops out in the Neuquén basin, Argentina, and represents one of the most important unconventional hydrocarbon reservoirs in the world. The Vaca Muerta Formation bears ammonites and calpionellids among the most important fossils for dating purposes; therefore the importanceof obtaining a robust magnetostratigraphy in this unit. In the Arroyo Loncoche section, the Vaca Muerta Formation is up to c.280 m-thick bearing ammonites from the Andean Region. 450 specimens were collected from 55 paleomagnetic sites were analysed, and the primary origin of the isolated magnetization proved through several field tests. Polarities were dated with ammonites and thus, a magnetostratigraphic scale was constructed and correlated with the International Geomagnetic Polarity Time Scale. Two independent chronostratigraphic tools such as cyclostratigraphy and magnetostratigraphy, were therefore used to successfully define the position of the J-K. This position is consistent with the magnetostratigraphic scales obtained in other sections of the Neuquén basin.